ATROPHIC GLOSSITIS AS A CLINICAL SIGN FOR ANEMIA IN THE ELDERLY (Case report) - Rahmatia Djou; Indah Suasani Wahyuni (Dentino : Jurnal Kedokteran Gigi, 2019)
Background: Atrophic glossitis is caused by nutritional deficiencies and this condition commonly affects elderly patients. It may be the first sign of more serious systemic diseases or condition like anemia. Aim: Describe about the atrophic glossitis in an elderly woman as a first clinical sign of anemia and the treatment. Case:  The patient was a 74-year-old woman with complaints of pain, burning sensation and numb of the tongue for the last 3 months. The patient has gone to the general dentist and given some medicines but the complaint still persists. Case management: Extra oral examination showed the conjunctiva was anemic, and from intraoral examination found depapillated and glossy tongue. Then the laboratory tests showed haemoglobin, haematocrite and the number of erythrocytes were decreased, while MCV and MCH level were increased. The patient's tongue abnormalities were diagnosed as atrophic glossitis associated with anemia Vitamin B (B12 dan folate) deficiencies. Patients were given high dose of folic acids and vitamin B12 per oral, and mouthwash containing hyaluronic acid as anti inflammation alternating with chlorhexidine gluconate 0,2% mouthwash as an antiseptic. The tongue was repaired after 1 month therapy and healed in 2 months. Discussion: Atrophic glossitis is considered as one of the the clinical signs of anemia, that appears as areas of complete or irregular partial loss of papillae of the tongue, which is caused by atrophy of the lingual papillae. The analysis of the appropriate diagnose and causative factors can be assisted through a complete blood examination and will help us to decide the appropriate therapy. Conclusion: Dentists must be aware of the clinical signs of atrophic glossitis, because it can be an indication of a major health problem especially anemia.